2011
DOI: 10.1364/ol.36.000799
|View full text |Cite
|
Sign up to set email alerts
|

Improving the brightness of a multi-kilowatt single thin-disk laser by an aspherical phase front correction

Abstract: We report on results obtained with an aspherical mirror to compensate for the phase front aberrations of a cw thin-disk laser with a single disk in the resonator. A record output power of 5 kW with a beam quality suitable for laser cutting (beam propagation factor M2=9.2) has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…The applied pressure of three bar at this power level corresponds to a step height on the deformable mirror of about 130 nm. Within the measurement uncertainties, this agrees well with the measured phase distortions of a similar thin-disk setup reported in [4].…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The applied pressure of three bar at this power level corresponds to a step height on the deformable mirror of about 130 nm. Within the measurement uncertainties, this agrees well with the measured phase distortions of a similar thin-disk setup reported in [4].…”
supporting
confidence: 89%
“…To achieve power scaling to the kW-range, it is therefore necessary to actively compensate for these wavefront deformations. For low-order multimode operation (M 2 < 10), it has been demonstrated that by means of an aspherical intracavity-mirror featuring a static step-like surface shape the aspheric wavefront deformations can be compensated for at a fixed power level [4]. In this way, up to 5 kW of output power from a single disk was demonstrated with a M 2 of 9.2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the strong signal confinement, their use is limited by the damage threshold of the facets and nonlinear effects such as stimulated Raman scattering, self-phase modulation, and self-focusing in the pulsed regime [1]. The thin-disk technology does not exhibit this limitation in the pulsed regime but suffers from relatively low axial gain limited by amplification of spontaneous emission in the transverse direction gain due to the crystal geometry [2], leading to limited energy per pulse and to complex multipass or regenerative amplifier setups. Finally, the slab technology has recently shown clear competitive advantages with over 1 kW of average output power obtained in the subpicosecond regime and 80 MW peak power [3].…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated, 8 that the aspherical phase distortions introduced by a pumped thin-disk laser crystal can be statically compensated for in a defined power range by the use of an intra-cavity aspheric mirror with a top-hat shaped surface contour matching the mode size on the mirror. Output powers of as high as 5 kW have been achieved from a single disk at M 2 < 10.…”
Section: Design Of the Deformable Mirrorsmentioning
confidence: 99%